2014
DOI: 10.1007/s10841-014-9671-3
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on sampling intensity of bees (Hymenoptera: Apoidea: Apiformes)

Abstract: Changes in bee fauna, such as the disappearance of certain species or increasing abundance of others, are very important. The common belief that pollinating insects are facing problems also prompts detailed studies of the bee fauna in order to track on-going changes. Assessment of the state of bee communities in particular ecosystems or ecosystem complexes within a landscape, tracing the course of trends in fauna and also predicting their future structures resulting from current changes, are only possible if s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…The order of site visits was randomised to ensure that all sites would receive roughly equal morning and afternoon sampling. High frequency surveys throughout the season are particularly important to record rare species and species that are active over a short period (Magurran and McGill 2011;Banaszak et al 2014). The 15 days of observation (hand net plus pan traps) was combined to make a single sampling unit for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The order of site visits was randomised to ensure that all sites would receive roughly equal morning and afternoon sampling. High frequency surveys throughout the season are particularly important to record rare species and species that are active over a short period (Magurran and McGill 2011;Banaszak et al 2014). The 15 days of observation (hand net plus pan traps) was combined to make a single sampling unit for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…We understand that the no difference on observed richness can be attributed to the sampling insufficiency. The twice-amonth proportion of observed and estimated number of species (60%) is lower than the 65% obtained by Banaszak et al (2014) but the percentage of the once-a-month subsets (39%) can be considered very low and therefore non representative of the community. The same overall pattern described here for aculeates was observed for bees, the most common group within the samples.…”
Section: Discussionmentioning
confidence: 61%
“…Studies on bowl trap methodology have focused in different colour preferences (e.g., ABRAHAMCZYK et al, 2010;HENEBERG & BOGUSH, 2014;MOREIRA et al, 2016), and only one study compared diversity and richness under different sampling intervals. Banaszak et al (2014) found more bee species using weekly sampling intervals during the flowering season in Poland, ensuring the collection of about 75% of estimated species number. However, studies in tropical regions with a more continuous and extended plant blooming pattern are completely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…2.25 ± 0.35) and their location in the school. Participants were asked to make, under suitable weather conditions (minimum of 15 °C, low wind, no rain), one 24-h capture session each month from March to October, in order to obtain an overall assessment of the bee assemblage composition over the whole flying season (Banaszak et al 2014). In practice, some participants could not carry out the required number of sessions or others made more than one session in a month.…”
Section: Bee Sampling and Identificationmentioning
confidence: 99%